Endogenous divorce and human capital production - Amanda Gosling; María D. C. García-Alonso (University of Kent, School of Economics, 2015)
This paper presents a model of parental decision making where parents care about consumption and the human capital of the children. Preferences over these goods can differ within households. Parents will agree to cooperate (stay married) if the utility they get from coordinating time inputs (ie child care or paid employment) is greater than they would get if they acted independently. The gain to cooperation arises because parental time inputs are not perfect substitutes in the production of the child's human capital, the cost is that when preferences differ, the chosen time allocations under cooperation may be very different to those chosen independently. Our model predicts that the human capital of children can both increase and fall after divorce. Divorce, if it occurs, will be instigated by the parent who cares most about the child, the parent that cares least about the child will never opt for divorce. This can explain the apparent contradiction that mothers are more likely than fathers to initiate divorce beyond infant age even though the traditional household literature presents women as home makers and ever devoted to household production.
Keywords: C79; D19; J12; J22; 330; collective model; human capital; divorce